Clinical and histological evaluation on application of platelet concentrates on depigmented gingival epithelium - Koel Debnath; Anirban Chatterjee (Wolters Kluwer Medknow Publications, 2018)
Background: The platelet concentrate is a windfall in the field of regenerative therapy in periodontology. It accelerates wound healing by excellent neovascularization and promoting fast cicatricle tissue remodeling. Aim: This study aims to evaluate clinically and histologically accelerated effect of platelet-rich fibrin (PRF) membrane and PRF matrix (PRFM) following depigmentation procedure. Materials and Methods: Eleven individuals were divided into three groups after depigmentation procedure. PRF membrane and PRFM gel were prepared as per standard protocol. Group A and B received PRF membrane and PRFM gel followed by periodontal dressing, respectively, and the only periodontal dressing was placed in Group C. The individuals were evaluated for visual analog scale (VAS) and healing index (HI) on 3rd and 5th day. Epithelization test and histologic analysis from punch biopsy were done on the 5th day. At 3rd month, reevaluation was performed. Results: The intergroup statistical analysis in respect to VAS, HI, epithelization test, and histologic analysis showed a statistically significant results with P < 0.001 in Groups A and B compared to Group C. Clinical evaluation of epithelization test and histologic analysis revealed better-wound healing and moderate to no inflammatory cell infiltrate in Groups A and B, respectively, as compared to Group C, which appeared more erythematous with dense inflammatory cells. Conclusion: Thus, the application of PRF membrane and PRFM gel has shown a successful approach to protect the raw wound area of depigmented sites with better patient comfort and faster healing.